Hospitalisation among immigrants in Italy - Cacciani, Laura; Baglio, Giovanni; Rossi, Lorenza; Materia, Enrico; Marceca, Maurizio; Geraci, Salvatore; Spinelli, Angela; Osborn, John; Guasticchi, Gabriella (Emerging Themes in Epidemiology, 2006)
Immigration is increasing in Italy. In 2003, 2.6 million foreign citizens lived in the country; 52% were men and the majority were young adults who migrated for work. The purpose of this study was to investigate differences in hospitalisation between immigrants and the resident population during the year 2000 in the Lazio region.